Cytotoxic of Ganoderma lucidum in Colon Cancer through Cyclooxygenase 2 (COX-2) as Its Molecular Target - Setiawati, Agustina (Journal of Tropical Life Science, 2017)
Many studies were designed explore chemopreventive activity of natural products on colon cancer especially addressing COX-2 as molecular target. Another promising source of natural product that potentially exhibit anticancer activity on colon cancer is Ganoderma lucidum. This study assessed selectivity of cytotoxic effect of G. lucidum extract on WiDr to Vero cells and investigated molecular mechanism on COX-2. G. lucidum ex-tract was prepared by reflux extraction method; in vitro anticancer was assayed by MTT method on WiDr and Vero cell line. This study applied apoptosis induction assay to observe cell death mechanism using double staining method; further COX-2 expression was stained by immunocytochemistry method. G. lucidum extract has cytotoxic effect on WiDr cells with IC50 135 Âµg/mL. However, the cytotoxic effect had low selectivity to-wards Vero cells with Selectivity Index (SI) 3.66. The extract induced apoptosis and suppressed COX-2 ex-pression in WiDr cells. G. lucidum extract was potential to be developed as anticancer agent towards colon cancer.